PERENCANAAN DRAINASE PERUMAHAN POGOH RESIDENCE 2 KELURAHAN TANJUNG PAKU, KOTA SOLOK - Beni Firdaus; Deddy Kurniawan; Selpa Dewi (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2023)
Abstract: Drainage has the meaning of draining, draining, dumping, or diverting water. In general, drainage is defined as a series of water structures that function to reduce or remove excess water from an area or land, so that the land can be used optimally. Drainage is also defined as an attempt to control groundwater quality in relation to salinity. The purpose of this study is to plan the drainage of Pogoh Residence 2 Housing, Tanjung Paku Village, Solok City. The data or information used is secondary data obtained from Tanjung Paku Village and primary data obtained from direct surveys in the field. So it is necessary to plan an economical drainage dimension that can drain water more optimally with a smaller cross-sectional pressure or drainage wall for the Pogoh Residence 2 Housing area with a trapezoidal channel type. After analyzing the calculation, it is found that the flow rate Q = 0.60 m³/sec with the top width b1 = 0.30 m, height h = 0,40 m, bottom width b2 = 0.25 m and flood water discharge for a 10 year return period. is Qmax = 0.54 m³/s. The data processing method uses manual calculations in accordance with the Gumbel Method, Rational Method and Haspers Method. to calculate the rain discharge, and the Manning formula for channel discharge.Keywords: Gumbel, Rational, Haspers, Trapezoidal Drainage Methods.